Continuity Editing on Fiction Movie Bhâko - Mochamad Ariyanto; Dwi Haryanto; Didik Suharijadi (ROLLING, 2019)
Bhâko portrayed the difficulty of tobacco peasant in Jember. The editor took editing as a major theory which using continuity editing. This technique was used to visualize the habit and conflict of tobacco farmer in Jember that the audience could feel those situations. Moreover, The editor applied several aspects of continuity editing such as 180-degree rules, shot/reverse shot, eyeline match, establish, match on action, point of view, cut-in, crosscutting, and montage sequence. In addition, match on look and match on dialogue were used as supporting techniques. Bhâko uses multiple plot lines. Thus, continuity techniques are suitable for editing each situation and atmosphere, also control the mood in each scene.